ChemInform Abstract: Two Self‐Assembled Water Clusters Stabilized by Cu‐Containing Compounds Based on MoO42‐. Issue 41 (October 2015) - Kuang, Ye; Yang, Bing; Pan, Jiali; Meng, Xianggao; Xiao, Fengping
Abstract Compounds (III) and (IV) are characterized by single crystal XRD, FTIR, and UV/VIS spectroscopy.